2023
DOI: 10.1093/nar/gkad107
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic YAP mediates changes in chromatin accessibility and activity that drive cell cycle gene expression and cell migration

Abstract: YAP, the key protein effector of the Hippo pathway, is a transcriptional co-activator that controls the expression of cell cycle genes, promotes cell growth and proliferation and regulates organ size. YAP modulates gene transcription by binding to distal enhancers, but the mechanisms of gene regulation by YAP-bound enhancers remain poorly understood. Here we show that constitutive active YAP5SA leads to widespread changes in chromatin accessibility in untransformed MCF10A cells. Newly accessible regions includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…On the other hand, YAP still forms around 15 condensates in confluent cells when they are supposedly inactive. While previous studies have shown that YAP is still able to bind to the chromatin under inactive conditions, 54 , 55 we speculate that YAP condensates in YAP-inactive condition may bookmark the important genes and prepare them for transcriptional activation once cells are placed sparsely and YAP becomes active. This is similar to the scenario when the TF Sox2 (SRY-box 2) binds to the mitotic chromosome in mouse embryonic stem cells and prepare the cells for transcription once mitosis ends.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, YAP still forms around 15 condensates in confluent cells when they are supposedly inactive. While previous studies have shown that YAP is still able to bind to the chromatin under inactive conditions, 54 , 55 we speculate that YAP condensates in YAP-inactive condition may bookmark the important genes and prepare them for transcriptional activation once cells are placed sparsely and YAP becomes active. This is similar to the scenario when the TF Sox2 (SRY-box 2) binds to the mitotic chromosome in mouse embryonic stem cells and prepare the cells for transcription once mitosis ends.…”
Section: Discussionmentioning
confidence: 56%
“…Deregulation of the Hippo pathway results in the dephosphorylation and nuclear localization of YAP to control the expression of cell cycle regulators and accelerate the growth of tumor cells. [ 30 ] In the present study, we showed that DNMT3A interacts with YAP/TAZ but does not modulate YAP/TAZ expression or cytoplasmic sequestration, revealing a Hippo pathway‐independent role for YAP in recruiting DNMT3A access to specific genome locations. In addition, our findings regarding the inconsistent function of DNMT3A and YAP in GBC growth led us to speculate that YAP‐induced expression of cell cycle regulators might not rely on DNMT3A‐mediated DNA methylation, which needs to be further explored.…”
Section: Discussionmentioning
confidence: 57%
“…Despite the fact that HIPPO pathway or YAP mediated alterations in chromatin accessibility have received great attention in recent studies, , it remains unclear whether active YAP can facilitate histone modifications at specific differentiation gene promoters in response to topographical or mechanical cues. …”
Section: Resultsmentioning
confidence: 99%
“…81 The nuclear transportation and activation of YAP/TAZ can cause histone acetylation by the related lysine acetyltransferases CBP and p300. 82 Despite the fact that HIPPO pathway or YAP mediated alterations in chromatin accessibility have received great attention in recent studies, 83,84 it remains unclear whether active YAP can facilitate histone modifications at specific differentiation gene promoters in response to topographical or mechanical cues. 85−87 Here, we hypothesize that YAP, together with other nuclear proteins, may regulate histone modification and expression of differentiation related genes in the mechanotransduction processes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%